Structural change and economic growth in China - Fan, Shenggen; Zhang, Xiaobo; Robinson, Sherman (Wiley, 2003)
This study develops a new analytical framework to account for sources of rapid economic growth in China. The traditional Solow approach is expanded to include another source of economic growth—structural change. The empirical results show that structural change has contributed to growth significantly by reallocating resources from low‐productivity sectors to high‐productivity sectors. It is found that the returns to capital investment in both agricultural production and rural enterprises are much higher than those in urban sectors, indicating underinvestment in rural areas. On the other hand, labor productivity in the agricultural sector remains low, a result of the still large surpluses of labor in the sector. Therefore, further development of rural enterprises and an increase in labor flow among sectors and across regions are key to improvements in overall economic efficiency.